The Potential for Genotoxicity, Mutagenicity and Endocrine Disruption in Triclosan and Triclocarban Assessed through a Combination of In Vitro Methods - Chrz, Jan; Dvořáková, Markéta; Kejlová, Kristina; Očadlíková, Danuše; Svobodová, Lada; Malina, Lukáš; Hošíková, Barbora; Jírová, Dagmar; Bendová, Hana; Kolářová, Hana (Journal of xenobiotics, 2023)
Triclosan and Triclocarban, preservatives widely used in cosmetics and other consumer products, underwent evaluation using a battery of new-approach methodologies in vitro (NAMs). Specifically, the Microplate Ames Test (MPFTM Test, Xenometrix, Allschwil, Switzerland) was employed to assess mutagenicity, the Comet assay in vitro on the HaCat cell line and the Mammalian Chromosome Aberration Test were utilized to evaluate genotoxicity, and the XenoScreen® YES/YAS assay was applied to investigate endocrine disruption. The chemicals did not exhibit any positive responses for mutagenicity. However, the mammalian chromosome aberration test identified both chemicals as being positive for genotoxicity at 10 μg/mL. In the Comet assay, the percentage of DNA in the tail significantly increased in a concentration-dependent manner (at 5 and 10 μg/mL for Triclosan, at 2.5, 5, and 10 μg/mL for Triclocarban). The positive response depended on the increasing concentration and the duration of exposure. Triclosan, but not Triclocarban in any of the endocrine assays performed, indicated a potential for endocrine activity in the anti-estrogenic and anti-androgenic assays. The positive in vitro results detected were obtained for concentrations relevant to final products. The alarming findings obtained with the use of new-approach methodologies (NAMs) justify the current precautionary regulatory approach, limiting the use of these preservatives.